From Formal Semantics to Verified Slicing : A Modular Framework with Applications in Language Based Security (2011)
This book presents a modular framework for slicing in the proof assistant Isabelle/HOL which is based on abstract control flow graphs. Building on such abstract structures renders the correctness results language-independent. To prove that they hold for a specific language, it remains to instantiate the framework with this language, which requires a formal semantics of this language in Isabelle/HOL. We show that formal semantics even for sophisticated high-level languages are realizable.